Kinglake pioneering days. Volume 2 - Hawkins, Deidre G. (Kinglake, [Victoria] : Kinglake Historical Society, 2013)
Pioneering days volume 2 records the stories of families who came to the Kinglake district in the early days of settlement. Where possible, the stories have been extended to show the linked between families.
Keywords: Families -- Victoria -- Kinglake; Pioneers -- Victoria -- Kinglake; Frontier and pioneer life -- Victoria -- Kinglake; Kinglake (Vic.) -- History; Australian